2019
DOI: 10.3390/children6080094
|View full text |Cite
|
Sign up to set email alerts
|

Applying Trauma-Informed Practices to the Care of Refugee and Immigrant Youth: 10 Clinical Pearls

Abstract: Immigrant and refugee youth have higher rates of trauma than youth who are not transnational. While youth are incredibly resilient, trauma and toxic stress can result in poor health outcomes that persist throughout life. However, clinical interventions can promote resilience and decrease the negative impact of trauma. This article will review the principles of trauma-informed care and its application for the care of immigrant and refugee youth and their families by sharing concrete and feasible strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…It was felt that CSOs, local NGOs and faith-based organisations provided an important role in assisting to instil hope among refugees. Psychologically being able to build trusting relationships following traumatic experiences with a trusted confidant, including friends and families, as well as individuals in organisations, is an important part of processing and healing traumatic experiences and building resilience in refugees [27]. Refugee survivor groups were formed in the refugee settlements by such organisations and were reported by refugees to be very helpful for connecting with others who had similar experiences, validation, psycho-education and sharing [28].…”
Section: Instil Hopementioning
confidence: 99%
“…It was felt that CSOs, local NGOs and faith-based organisations provided an important role in assisting to instil hope among refugees. Psychologically being able to build trusting relationships following traumatic experiences with a trusted confidant, including friends and families, as well as individuals in organisations, is an important part of processing and healing traumatic experiences and building resilience in refugees [27]. Refugee survivor groups were formed in the refugee settlements by such organisations and were reported by refugees to be very helpful for connecting with others who had similar experiences, validation, psycho-education and sharing [28].…”
Section: Instil Hopementioning
confidence: 99%
“…Self-report questionnaires may be subject to issues of over- and underreporting of symptoms; most research has found that self-report questionnaires overreport symptoms ( Charlson et al, 2019 ). It should be noted that possible indications for PTSD based on the UCLA PTSD RI may not accurately capture possible presence of a disorder given that youth rarely screen positive on this measure because the criteria have been derived from adult populations ( Copeland et al, 2007 ; Cohen et al, 2008 ; Miller et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A symptom is “present” if the symptom score is 3 or 4, with the exceptions of questions 4, 10, and 26, where a rating of 2 or more is indicative of symptom presence ( Steinberg et al, 2004 , 2013 ). The UCLA PTSD RI has been recommended for use with refugee populations, including those with non-Western backgrounds ( Miller et al, 2019 ), and has been found to be reliable ( Javanbakht et al, 2018 ). Cronbach’s alpha for the UCLA in this sample was.946, representing a high degree of internal consistency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack in the provision of linguistic support for asylum seekers has many negative consequences. In addition to misinformation and confusion, it can lead to a drop-out of the use of their services (Arias-Badia and Jiménez-Andrés, 2021), to an accentuation of their current vulnerabilities or to re-traumatisation (Gardiner and Walker, 2019;Miller et al, 2019).…”
Section: The Role Of Ngos and Translation And Interpreting In The Recmentioning
confidence: 99%